EFEKTIVITAS MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN SBdP SISWA KELAS III SDN 007 SUNGAI KUNJANG - Muhlis Muhlis; Inthan Azzahra Inthan; Rosita Putri Rahmi; Sainal A; Muhammad Sultan (STKIP Subang, 2023)
SBdP learning in class III at SDN 007 Sungai Kunjang is not yet effective, resulting in students' SBdP learning outcomes not being optimal. Therefore, to create meaningful SBdP learning, teachers must design learning models that are appropriate to SBdP learning. This research aims to determine the effectiveness of the model Project Based Learning in improving SBdP learning outcomes in the material of making collage works for class III students at SDN 007 Sungai Kunjang. The research method used is the experimental method. The research design used is pre-experimental design with shapes one group pretest posttest design. The population in this study were class III students at SDN 007 Sungai Kunjang. The sampling technique used is engineering simple random sampling. The instrument of this research is a test instrument in the form of multiplechoice questions. The data analysis techniques used include Validity Test, Reliability Test, Normality Test and Hypothesis Test. Based on the results of the research conducted, the research results concluded that SBdP learning uses a learning model Project Based Learning class III B at SDN 007 Sungai Kunjang got an average score of 82.59, while SBdP learning without using a learning model got an average score of 62.96. Learning model Project Based Learning effective in improving student learning outcomes, this is proven from the Test calculation paired sample T-test shows that the price t-calculation is greater than the price t-table (6,263 > 2,056) and significance value (0.00 < 0.05). So it is declared proven to be true. Thus, the learning modelProject Based Learning declared effective in improving student learning outcomes in the SBdP subject for class III students at SDN 007 Sungai Kunjang.